2009
DOI: 10.1093/jac/dkn542
|View full text |Cite
|
Sign up to set email alerts
|

SXT-related integrating conjugative element and IncC plasmids in Vibrio cholerae O1 strains in Eastern Africa

Abstract: This study has shown the spread of SXT-related ICEs among V. cholerae O1 African isolates. It has also highlighted the role of two distinct genetic elements in conferring multiple resistance to the two distinct groups of V. cholerae O1 strains that, in the late 1990s, spread through Eastern Africa, a critical geographic region for the persistence and transmission of cholera to the entire continent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 8 publications
1
28
0
2
Order By: Relevance
“…Few previous surveys analyzed the prevalence of this family of ICEs, and they were limited to clinical isolates related to V. cholerae. Those studies reported the spread of ICE-harboring V. cholerae strains in Eastern Africa during the late 1990s (29) and also in India from 1994 to 2005 (10). Therefore, our results and previous data exhibited similar trends, indicating a gradual emergence of SXT/R391-like ICEs in bacteria of different environments and locations.…”
Section: Discussionsupporting
confidence: 88%
“…Few previous surveys analyzed the prevalence of this family of ICEs, and they were limited to clinical isolates related to V. cholerae. Those studies reported the spread of ICE-harboring V. cholerae strains in Eastern Africa during the late 1990s (29) and also in India from 1994 to 2005 (10). Therefore, our results and previous data exhibited similar trends, indicating a gradual emergence of SXT/R391-like ICEs in bacteria of different environments and locations.…”
Section: Discussionsupporting
confidence: 88%
“…the cephalosporin resistance gene bla CMY-2 16 and rifampicin resistance gene)13. In this study, isolates positive for resistant related genes at SXT/R391 ICEs were not always consistent with their phenotypic resistance (Table 1), this result indicated the phenotypic resistance may not be associated with genes encoded by ICEs, determinants of other mobile genetic elements, like plasmid36, transposon37 and genomic island38 within Enterobacteriaceae , are also mediated drug resistance. However, the role of ICEs in the acquisiton and transmission of antibiotic resistance should not be neglected, our study have displayed high transfer ability of ICEs from Proteus isolates to recipient cells.…”
Section: Discussionmentioning
confidence: 60%
“…Kenyan isolates also lacked the dfrA18 gene (Kiiru et al, 2009). Since the emergence of SXT in V. cholerae O139, several studies on V. cholerae O1 have found this ICE as responsible for the dissemination of antibiotic resistance in Africa and Asia (Dalsgaard et al, 2001; Amita et al, 2003; Opintan et al, 2008; Adabi et al, 2009; Pugliese et al, 2009). ICEs of the SXT/R391 family are usually found in atypical O1 El Tor V. cholerae epidemic strains; they confer a narrow antibiotic resistance profile (Wozniak et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Superintegrons are the ancestors of multiresistant integrons (Mazel, 2006). Integrons and ICEs have been found in V. cholerae isolated in Mozambique, Iran, and India and they have largely contributed to the spread of antibiotic resistance (Amita et al, 2003; Adabi et al, 2009; Pugliese et al, 2009). …”
Section: Introductionmentioning
confidence: 99%